GLOBAL STRUCTURAL ANALYSIS OF HIGH-RISE HOSPITAL BUILDING USING EARTHQUAKE RESISTANT DESIGN APPROACH - Ayuddin Ayuddin (SINERGI, 2020)
Building designed has 1 to 8 floors with the quality of concrete f'c of 33.2 MPa, steel quality (fy) 400 MPa, and shear stress of 240 MPa. The building is analyzed by 3D structure modeling through ETABS Version 9.7 program by following all the rules and regulations applicable in Indonesia, such as the guidance of building structure and non-building, SNI 1726: 2012. This building design system is a high-rise building structure planned with a portal frame system with beams and columns as the main elements of structures made of conventional concrete. The beam carries the load transversely of its length and transfers the load to the vertical columns that accumulate it. The column accepts the load axially by the beam and transfers the load to the foundation. This building structure uses a special moment frame structure system (SRPMK) structure, considering that the hospital building is safe against earthquakes and complains about the strong column weak beam concept.